Farm Record Keeping - Schlender, John R. (My University, 1991)
This publication is a textbook for keeping records in the Kansas Farm Account Book. It explains each of the basic parts of the book and gives instructions on the kind of information to record and how it is to be recorded.
MF408_1991_11
Keywords: MF408; Economics; Equipment and Structures; MF